Piezo1 Mechanosensitive Ion Channel Mediates Stretch-Induced Nppb Expression in Adult Rat Cardiac Fibroblasts - Meike C. Ploeg; Chantal Munts; Frits W. Prinzen; Neil A. Turner; Marc van Bilsen; Frans A. van Nieuwenhoven (Cells, 2021)
In response to stretch, cardiac tissue produces natriuretic peptides, which have been suggested to have beneficial effects in heart failure patients. In the present study, we explored the mechanism of stretch-induced brain natriuretic peptide (Nppb) expression in cardiac fibroblasts. Primary adult rat cardiac fibroblasts subjected to 4 h or 24 h of cyclic stretch (10% 1 Hz) showed a 6.6-fold or 3.2-fold (p < 0.05) increased mRNA expression of Nppb, as well as induction of genes related to myofibroblast differentiation. Moreover, BNP protein secretion was upregulated 5.3-fold in stretched cardiac fibroblasts. Recombinant BNP inhibited TGFβ1-induced Acta2 expression. Nppb expression was >20-fold higher in cardiomyocytes than in cardiac fibroblasts, indicating that cardiac fibroblasts were not the main source of Nppb in the healthy heart. Yoda1, an agonist of the Piezo1 mechanosensitive ion channel, increased Nppb expression 2.1-fold (p < 0.05) and significantly induced other extracellular matrix (ECM) remodeling genes. Silencing of Piezo1 reduced the stretch-induced Nppb and Tgfb1 expression in cardiac fibroblasts. In conclusion, our study identifies Piezo1 as mediator of stretch-induced Nppb expression, as well as other remodeling genes, in cardiac fibroblasts.